Immune activation and HIV persistence: implications for curative approaches to HIV infection - Klatt, Nichole R.; Chomont, Nicolas; Douek, Daniel C.; Deeks, Steven G. (Immunological reviews, 2013)
Summary Despite complete or near‐complete suppression of human immunodeficiency virus (HIV) replication with combination antiretroviral therapy, both HIV and chronic inflammation/immune dysfunction persist indefinitely. Untangling the association between the virus and the host immune environment during therapy might lead to novel interventions aimed at either curing the infection or preventing the development of inflammation‐associated end‐organ disease. Chronic inflammation and immune dysfunction might lead to HIV persistence by causing virus production, generating new target cells, enabling infecting of activated and resting target cells, altering the migration patterns of susceptible target cells, increasing the proliferation of infected cells, and preventing normal HIV‐specific clearance mechanisms from function. Chronic HIV production or replication might contribute to persistent inflammation and immune dysfunction. The rapidly evolving data on these issues strongly suggest that a vicious cycle might exist in which HIV persistence causes inflammation that in turn contributes to HIV persistence.